Lung volume recruitment acutely increases respiratory system compliance in individuals with severe respiratory muscle weakness - Yannick Molgat-Seon (ERJ Open Research, 2017)
The aim of the present study was to determine whether lung volume recruitment (LVR) acutely increases respiratory system compliance (Crs) in individuals with severe respiratory muscle weakness (RMW). Individuals with RMW resulting from neuromuscular disease or quadriplegia (n=12) and healthy controls (n=12) underwent pulmonary function testing and the measurement of Crs at baseline, immediately after, 1 h after and 2 h after a single standardised session of LVR. The LVR session involved 10 consecutive supramaximal lung inflations with a manual resuscitation bag to the highest tolerable mouth pressure or a maximum of 50 cmH2O. Each LVR inflation was followed by brief breath-hold and a maximal expiration to residual volume. At baseline, individuals with RMW had lower Crs than controls (37±5 cmH2O versus 109±10 mL·cmH2O−1, p<0.001). Immediately after LVR, Crs increased by 39.5±9.8% to 50±7 mL·cmH2O−1 in individuals with RMW (p<0.05), while no significant change occurred in controls (p=0.23). At 1 h and 2 h post-treatment, there were no within-group differences in Crs compared to baseline (all p>0.05). LVR had no significant effect on measures of pulmonary function at any time point in either group (all p>0.05). During inflations, mean arterial pressure decreased significantly relative to baseline by 10.4±2.8 mmHg and 17.3±3.0 mmHg in individuals with RMW and controls, respectively (both p<0.05). LVR acutely increases Crs in individuals with RMW. However, the high airway pressures during inflations cause reductions in mean arterial pressure that should be considered when applying this technique.